Comparative analysis of outcomes following craniotomy and expanded endoscopic endonasal approach resection of tuberculum sellae meningiomas: a single-institution study - Feng, Zhenguang; Li, Chuzhong; Cao, Lei; Liu, Chunhui; Qiao, Ning; Wu, Wentao; Ma, Guofo; Gui, Songbai (Frontiers in Neurology, 2023)
Background: Traditionally, supratentorial craniotomy has been used to sever tuberculum sellae meningiomas (TSMs), but there has been a remarkably increasing tendency of extended endoscopic endonasal approach (EEEA) used to treat TSMs in recent decade. Several documents have described the advantages and disadvantages of both approaches, but there is not a consensus whether one is more superior to the other. Objective: To compare surgical outcomes between craniotomy and EEEA for TSMS treated at our institution. Methods: From January 2015 to December 2021, a total of 84 cases of TSMs were included in this study. Cases were separated into 2 groups: Craniotomy group and EEEA group. Their anamneses and surgical records were reviewed. Demographic data, presenting symptoms, tumor volume, extent of resection, visual outcomes and follow-up data were tabulated. The Kaplan-Meier curves were constructed for the PFS for both cohorts. Results: Complete data were available for 84 surgeries; 39 cases were treated via craniotomy, and 45 were treated via EEEA. Patient demographic data, preoperative symptoms, and tumor characteristics were similar between the 2 cohorts. The extent of resection was similar between the 2 groups (GTR: 91.11% EEEA vs 87.18% craniotomy; STR 8.89% vs 12.82%, p = 0.91). There was not difference in visual outcome between both groups (92.1% vs 84.84%, p=0.46). An increased rate of cranial nerve injury was noted in the craniotomy group (0% vs 10.25%, p = 0.04). Postoperative CSF leak rate occurred in one patient in the EEEA group. The PFS curves (p = 0.52) and recurrence/progression rates (13.33%vs 20.51%, p =0.39) were similar between the 2 groups. Conclusions: Both EEEA and craniotomy can successfully sever TSMs. The recurrence/progression rate and PFS appear to be similar between two groups. Although there are not differences in EOR and visual outcomes between two groups, there was a clear trend in the EEEA group to obtain a better outcome. CSF leakage was common in the EEEA cohort, whereas the rate of cranial nerve injury was found to be higher in the craniotomy cohort. We believe that our data support the conclusion that EEEA surgery is the preferred approach for removal of TSMs.